Reflecting upon students' problems in phonemic dictations - Grasso, Marina (2017)
Students of the Teacher education and Translation courses at the Universidad Nacional de La Plata, Argentina, receive a year training on the segmental features and another one on the suprasegmental features of English. Worried about the significant number of exams failed due to inaccurate transcriptions, we have qualitatively analysed the phonemic mistakes in students' dictations with the aim of helping learners correct their transcriptions once the acoustic stimulus is no longer available. We believe that during the revision stage students can use resources like contextual clues, their command of the language and their knowledge about the phonemic system of English to correct their transcriptions. We provide instances of frequent problems made evident in their exams and attempt to account for them. We also suggest some possible ways of helping learners improve their transcription skills, giving ideas on how to approach the correction stage before handing in their written tests.
Keywords: Phonemic transcriptions; Dictation; Revision stage